PISA Assessment on Reading Literacy Competency : Evidence from Students in Urban, Mountainous and Island Areas - Amir, Johar; Dalle, Ambo; Dj, Sulastriningsih; Irmawati, Irmawati (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to analyze the reading literacy competence of students in class VIII junior high school in Pangkajene and Islands Regency to find, understand, and evaluate information from reading texts. The research used the descriptive quantitative method. The population in this study were all class VIII students spread throughout Pangkajene and Islands Regency were divided into urban, mountainous and island areas totaling 114 schools where the sample selection used purposive sampling and cluster sampling techniques. The technique for collecting data is the test technique. The research instrument was PISA’s questions in 2021. The test PISA’s results showed that 26.7- 60% of students in Class VIII from the three schools in Pangkajene and Islands Regencies had very low competence in finding information, with a score of <54. Then in understanding the reading text, they could only obtain an average score of 33.03. As for the ability to evaluate text, 96.6% of students were in the low category, and only 3.4% were in the high category. This research indicated that students at the junior high school level needed the PISA assessment system to improve the quality of educational competence in Indonesia towards international education standards in the 21st century, especially in reading literacy. The PISA assessment focuses on improving the quality of teaching by teachers and learning in individual students. So that regular PISA assessments can help all students to achieve high competence if the government, school principals and teachers work together to implement and evaluate the PISA assessment on the reading literacy method.